Cellular distribution of secretory pathway markers in the haploid synergid cells of Arabidopsis thaliana. (9th March 2018) - Jones, Daniel S.; Liu, Xunliang; Willoughby, Andrew C.; Smith, Benjamin E.; Palanivelu, Ravishankar; Kessler, Sharon A.
Summary: In flowering plants, cell–cell communication plays a key role in reproductive success, as both pollination and fertilization require pathways that regulate interactions between many different cell types. Some of the most critical of these interactions are those between the pollen tube (PT) and the embryo sac, which ensure the delivery of sperm cells required for double fertilization. Synergid cells function to attract the PT through secretion of small peptides and in PT reception via membrane‐bound proteins associated with the endomembrane system and the cell surface. While many synergid‐expressed components regulating PT attraction and reception have been identified, few tools exist to study the localization of membrane‐bound proteins and the components of the endomembrane system in this cell type. In this study, we describe the localization and distribution of seven fluorescent markers that labelled components of the secretory pathway in synergid cells of Arabidopsis thaliana . These markers were used in co‐localization experiments to investigate the subcellular distribution of the two PT reception components LORELEI, a GPI‐anchored surface protein, and NORTIA, a MILDEW RESISTANCE LOCUS O protein, both found within the endomembrane system of the synergid cell. These secretory markers are useful tools for both reproductive and cell biologists, enabling the analysis of membrane‐associated trafficking within a haploid cell actively involved in polar transport. Significance Statement: Flowering plant reproduction requires the coordination of intercellular communication pathways between specialized cells regulating pollen tube attraction and reception. In this study, we generated a suite of fluorescent markers labeling key components of the secretory pathway and stably expressed them in the synergid cells of Arabidopsis thaliana, enabling the detailed analysis of the regulation of cellular trafficking in a haploid cell.